The N-terminal domain of Chlamydia psittaci Pmp19G modulates macrophage autophagy by targeting the NOD1 receptor and the ATG16L1–RAB7 signaling pathway - Li, Qiang; Wang, Huimin; Cui, Yuehui; Huang, Zongyang; Zhang, Xuedi; He, Rongze; He, Cheng (Frontiers in Immunology, 2025)
IntroductionChlamydia psittaci (C. psittaci), a zoonotic intracellular Gram-negative bacterium, is responsible for human infections presenting as flu-like fever and community-acquired pneumonia. Previous studies have implicated polymorphic membrane (Pmp) G in tissue tropism and induction of immune responses. However, the mechanisms by which Pmp19G promotes C. psittaci infection and immune evasion—especially via macrophage subversion remain poorly understood.Methods and ResultsThis study demonstrates that both C. psittaci and recombinant C. psittaci-specific Pmp19G protein activated autophagy in macrophages. This activation was characterized by increased autophagosome formation, conversion of LC3-I to LC3-II, and accumulation of p62/SQSTM1, while lysosomal associated membrane protein 1 (LAMP1), a late autophagy biomarker, remained unaffected. Utilizing pull-down assays coupled with co-immunoprecipitation, we identified the NOD1 receptor as an interactor with the N-terminal domain of Pmp19G. Subsequent analysis confirmed activation of the NOD1-ATG16L1 signaling pathway. NOD1 knockout or knockdown significantly impaired Pmp19G-mediated autophagic flux. Furthermore, treatment with Pmp19G enhanced the recruitment of RAB7 during the late stages of autophagy.DiscussionOur findings indicate that Pmp19G regulates macrophage autophagy through distinct mechanisms in early and late phases: activation of the NOD1-ATG16L1 signaling pathway initiates early autophagy, while enhanced RAB7 recruitment inhibits autophagosome-lysosome fusion during late autophagy. Collectively, Pmp19G-involved manipulation of the autophagic process represents a critical strategy employed by C. psittaci to evade host immune defenses, leading bacterial survival and spread.